2008
DOI: 10.1890/07-1216.1
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific Variation in a Predator Affects Community Structure and Cascading Trophic Interactions

Abstract: Abstract. Intraspecific phenotypic variation in ecologically important traits is widespread and important for evolutionary processes, but its effects on community and ecosystem processes are poorly understood. We use life history differences among populations of alewives, Alosa pseudoharengus, to test the effects of intraspecific phenotypic variation in a predator on pelagic zooplankton community structure and the strength of cascading trophic interactions. We focus on the effects of differences in (1) the dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

26
429
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 262 publications
(456 citation statements)
references
References 61 publications
26
429
0
1
Order By: Relevance
“…Similarly, alewives, guppies and salamanders have been shown to exhibit phenotypic variation stemming from evolution that has impacts on the abundances of associated species and ecosystem processes [5,9,11]. These findings reinforce that top-down control is a fundamental driver of community assembly and ecosystem function [4,12,13] and shed light on the role of intraspecific variation and evolutionary processes in the effects of predation [14,15].…”
Section: Introductionmentioning
confidence: 62%
“…Similarly, alewives, guppies and salamanders have been shown to exhibit phenotypic variation stemming from evolution that has impacts on the abundances of associated species and ecosystem processes [5,9,11]. These findings reinforce that top-down control is a fundamental driver of community assembly and ecosystem function [4,12,13] and shed light on the role of intraspecific variation and evolutionary processes in the effects of predation [14,15].…”
Section: Introductionmentioning
confidence: 62%
“…Guppy evolutionary history had significant effects on, for example, algal stock, gross primary production and biomass-specific productivity. Another example comes from a series of studies by Post and colleagues who tested for eco-evolutionary dynamics resulting from an initial ecological change in planktivore fish populations (landlocking of populations that originally were able to migrate between freshwater and marine environments, that is, anadromous alewives, Alosa pseudoharengus) [41][42][43] . Landlocked alewives exerted a constant grazing pressure on the zooplankton population throughout the year.…”
Section: Discussionmentioning
confidence: 99%
“…It is now well recognized that ecological factors, including human mediated environmental change, can cause rapid evolution, including diversification within species [4][5][6] . Recent studies have also shown the reciprocal, that the phenotypic variation that emerges on contemporary timescales can have strong effects on ecological processes 1,[7][8][9][10] . Strong effects of phenotypic variation in predators can propagate down through the food web affecting the ecology of species at multiple lower trophic levels [8][9][10][11][12] , and thereby cause a cascade of evolutionary change in prey species 12 .…”
mentioning
confidence: 99%